PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENINGKATAN PENGETAHUAN ANAK TENTANG COVID 19 DI SD NEGERI 2 KRUENG SABEE KABUPATEN ACEH JAYA - Mulfianda, Riyan; Desreza, Nanda; Munira, Misbahul (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
The spread of COVID-19 cases is increasing, it is necessary to prevent covid 19, especially for school children. The purpose of this study was to determine the effect of health education on increasing children's knowledge about covid 19 at SD Negeri 2 Krueng Sabee, Aceh Jaya Regency in 2021. This type of research was quasi-experimental using a one-group pretest posttest design, the study was carried out 6 to 19 April 2021. The population in this study were all fourth and fifth-grade school children at SD Negeri 2 Krueng Sabee, Aceh Jaya Regency using a purposive sampling technique as many as 20 people. The results showed that before the intervention, most of the children's knowledge was in the sufficient category as many as 11 respondents (55%) and in the good category only 1 respondent (5%), after the intervention most of the children's knowledge was in the good category as many as 9 respondents ( 45%) and in the sufficient category as many as 10 respondents (50%). The results of the analysis using the paired sample T-test obtained a p-value of 0.000 < = 0.05, so it can be concluded that there is an effect of health education on increasing children's knowledge about covid 19 before and after treatment. It is hoped that this research can provide significant information for teachers and UKS officers in conducting socialization for students in the school environment about the application of the practice of using masks, washing hands and social distancing during the pandemic.